Experimental and Theoretical Studies of Laser Desorption/Ionization of Methylene Blue from the Surface of Thermally Exfoliated Graphite - Gabovich, V.A.; Pokrovsky, V.A.; Demianenko, E.M.; Grebenyuk, A.G. (Ukrainian Journal of Physics, 2012)
Mass spectra of products obtained in the course of laser desorption/ionization of methylene blue from the surface of thermally exfoliated graphite have been registered. It is demonstrated that [M+1]+, [M+2]+, and [M+3]+ ions with one, two, or three, respectively, hydrogen atoms bound to the molecular ion dominate in the mass spectra. The experimental results are confirmed by quantum chemical calculations of possible reaction products that may be formed under the influence of laser radiation.